2020
DOI: 10.14710/dmj.v9i3.27497
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Body Mass Index to Acute Myocardial Infarction in-Hospital Patients Mortality Rate in Dr. Kariadi Hospital

Abstract: Introduction. Populations with high BMI are at risk for cardiovascular disease because these populations usually have high levels of fat in the body. In contrast, there are several studies that prove that body weight below normal BMI also increases cardiovascular disease risk and death. The aim of this study was to determine the impact of BMI on mortality rates of in-hospital patients with acute myocardial infarction at dr. Kariadi Hospital. Methods. This research is a retrospective analytic observational stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Chi-square test obtained mark p = 0.171. So, concluded that No there is connection between nutritional status with history chemotherapy in patients cancer breasts at Home Sick Ibn Sina Makassar, visible from trend patient with history chemotherapy who had good nutritional status (57.1% ) compared with nutritional status other.Study This support study previously carried out byAji et al (2020) at home Sick Dr. Kariadi Semarang. With design study cross sectional, retrieval sample done in a way consecutive sampling with a total of 29 samples.…”
supporting
confidence: 61%
“…Chi-square test obtained mark p = 0.171. So, concluded that No there is connection between nutritional status with history chemotherapy in patients cancer breasts at Home Sick Ibn Sina Makassar, visible from trend patient with history chemotherapy who had good nutritional status (57.1% ) compared with nutritional status other.Study This support study previously carried out byAji et al (2020) at home Sick Dr. Kariadi Semarang. With design study cross sectional, retrieval sample done in a way consecutive sampling with a total of 29 samples.…”
supporting
confidence: 61%